CONTINUITIES IN THE INTELLECTUAL AND POLITICAL MEXICAN DISCOURSE ON THE INDIGENOUS GROUPS IN THE NINETEENTH AND TWENTIETH CENTURY. (Tzintzun, Revista de Estudios Históricos, 2016)
This article analyzes the content of the public, political and intellectualdiscourse, on the indigenous groups along the history of México anindependent country to the 2000. In this work we propose that theassignment of indigenous identities across the public speech answers to theneeds of self perception, self identification and the construction of the State.This State creates ethnic identities according to the historical moment, aimingto construct the national project. In this present investigation there will befour types of discourse analyzed through the nineteenth and twentiethcentury, in which substantial changes are made in the rhetoric of the nationalproject, and when also variations in the way of perceiving, defining anddescribing indigenous groups occurred. In spite of the assumed changes,through the research, it is acknowledge that certain continuities prevail andremain.
Keywords: Mexico; indigenous; intellectual discourse; political discourse; liberalism; pluralism